The effect of volatility on anonymity broker ID in Indonesia Stock Exchange - Permanasari, Farah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This paper examines the the effect of volatility on anonymity Broker ID in order driven markets in Indonesia Stock Exchange. Previous theoretical research in Euronext Paris, the Tokyo Stock Exchange predicts that limit order anonymity results in deeper and more liquid markets. Indonesia Stock Exchange removed broker identifiers from limit orders on December 6, 2021, respectively. The results provide evidence that altering limit order anonymity has an impact on volatility. Accounting for fixed effects and endogeneity, we find increased volatility.